Fast screening of total nutrient contents in strawberry leaves and spent growing media using NIRS - Vandecasteele, Bart; Van Waes, Chris (Frontiers in Plant Science, 2023)
In soilless cultivation, the main nutrient sinks are nutrients retained either by the crop or in spent growing media. Measurement of nutrients in spent growing media and in the aboveground vegetative plant biomass at crop termination are a tool for assessing and optimizing nutrient efficiency. The first aim of this study was to test the potential of near-infrared reflectance spectroscopy (NIRS) to forecast the various nutrient contents in strawberry leaves, which would then allow for assessment of crop nutrient status and nutrient uptake by strawberry plants. A database with 369 dried and ground strawberry leaf samples with known contents of N, P, K, Ca, and Mg were scanned using NIRS. These samples originated from different trials and variable conditions including different growing media blends and a range of fertilizer types and doses. The resulting database covered a range of leaf contents of 0.6-3.5 %N/dry matter (DM), 0.7-6.3 g P/kg DM and 2-29 g K/kg DM. Validation indicated potential for this application, with R2 values of 0.90 or higher for N, K and Ca, and R 2 values higher than 0.85 for P and Mg. The second aim was to test NIRS as a high throughput technique for assessing the N, K, Ca, Mg and organic matter (OM) content and the pH, EC and C:N and C:P ratios for a dataset of composts, plant fibers and spent growing media. Validation indicated the potential for this application, with R2 values of 0.90 or higher for organic matter, and with R2 values of 0.85 or higher for total Ca, pH and C:N. P and K content and for C:P, electrical conductivity(EC) and total N. A first test indicated potential for the calibration based on fresh samples of compost, plant fiber as well as spent growing media or dried (not ground) samples. Use of NIRS on fresh samples would eliminate the need for drying and grinding the samples and would reduce screening time. The ammonium acetate extraction is a reliable alternative to NIRS for fast screening of the total P, K, Ca, and Mg contents in composts, plant fibers and spent growing media.